2013
DOI: 10.1021/jm301527r
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Pharmacological Properties of New Heteroarylpyridine/Heteroarylpyrimidine Derivatives as CB2 Cannabinoid Receptor Partial Agonists

Abstract: Recent developments indicate that CB(2) receptor ligands have the potential to become therapeutically important. To explore this potential, it is necessary to develop compounds with high affinity for the CB(2) receptor. Very recently, we have identified the oxazinoquinoline carboxamides as a novel class of CB(2) receptor full agonists. In this paper we describe the medicinal chemistry of a new series of heteroaryl-4-oxopyridine/7-oxopyrimidine derivatives. Some of the reported compounds showed high affinity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In this context, very recently we have reported the medicinal chemistry of a series of heteroaryl-4-oxopyridine/7-oxopyrimidine derivative as represented by trans -4,7-dihydro-1,3-dimethyl- N -(4-methylcyclohexyl)-4-oxo-7-pentyl-1 H -pyrazolo[3,4- b ]pyridine-5-carboxamide 5 ( Chart ), which displayed high affinity at the CB 2 receptor (hCB 2 K i = 11.4 nM, hCB 1 K i = 4568, SI = 401). In this study, additional CB 2 ligands were synthesized by replacing the pyrazolo ring with different heterocycles that were found to be potent CB 2 receptor ligands.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, very recently we have reported the medicinal chemistry of a series of heteroaryl-4-oxopyridine/7-oxopyrimidine derivative as represented by trans -4,7-dihydro-1,3-dimethyl- N -(4-methylcyclohexyl)-4-oxo-7-pentyl-1 H -pyrazolo[3,4- b ]pyridine-5-carboxamide 5 ( Chart ), which displayed high affinity at the CB 2 receptor (hCB 2 K i = 11.4 nM, hCB 1 K i = 4568, SI = 401). In this study, additional CB 2 ligands were synthesized by replacing the pyrazolo ring with different heterocycles that were found to be potent CB 2 receptor ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, on the one hand, our approach relied on the modification of the 4-quinolones into 4-hydroxy-2-quinolones, such as compound 2 , to obtain slightly acidic compounds with p K a values typically in the range 4.2–5.0 and hence expected to show better aqueous solubility at physiological pH. On the other hand, Aghazadeh Tabrizi et al opted for a scaffold hopping strategy, by replacing the benzene ring of 4-quinolones with pyrazole, giving rise to two isomeric series, namely, pyrazolo­[3,4- b ]­pyridine-5-carboxamides (e.g., 3 , Chart ) and pyrazolo­[1,5- a ]­pyrimidine-6-carboxamides . Both works led to some advances in terms of physicochemical optimization of the target cannabinoid ligands, associated with preservation of the binding affinity and receptor selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…To further explore structural diversity of the derivatives, the six member ring A of 1,8-naphthyridine was curtailed to five member ring imidazole, which the 1,8-naphthyridine-4(1 H )one-3-carboxamide scaffold switched to pyrazolo[5,4- b ]pyridin-4-one scaffold. 33 The results showed that the most obtained compounds exhibited more significant affinity and selectivity for CB2, particularly for 21. Moreover, they found that the functionality of these ligands was controlled by the nature of the heteroaryl function condensed with the pyridine ring.…”
Section: Strategies Of Optimizationmentioning
confidence: 94%